Evaluation rubric on student satisfaction in a Peruvian university - Rojas Galarza, Julio Ernesto (2022)
The purpose of the study was to determine the impact of the use of evaluation rubrics to measure satisfaction levels of university students in Peru. The method belongs to the quantitative route, causal correlational level, non-experimental, hypothetical deductive method, the study group was represented by 83 university students. The information collection questionnaires were outlined for each variable using the Likert scale; it was carried out through the virtual survey technique through Google forms. The results obtained demonstrated a Wald value of 9.541, far from 0, which indicates that there is an effect between the variables with a p value = 0.002 at least 0.05. The result is objected to the null assumption and the alternative assumption is admitted. The study concluded that the application of evaluation rubrics significantly impacts the complacency of university students as service agents.